"Sunda modern"; Gendered modernity in Sundanese performing arts - Weintraub, Andrew N. (Wacana, Journal of the Humanities of Indonesia, 2025)
In this article, I offer new ways of seeing and hearing Sundanese women singers in modern post-independence Indonesia. I propose a dynamic and historical approach to show how individual female singers shaped new material realities and symbolic meanings of modern Sundanese identity (Sunda modern) from the early 1950s through the mid-1970s. My approach emphasizes difference, uniqueness, and novelty in singers’ public image, on-stage presentation, vocal style, and musical repertoire. I contend that singers’ ability to branch out and cross over – by engaging the national (for example, singing in the national language) and the global (for example, Western-inflected genres) – structured a modern feeling of Sundanese-ness that was emergent (but not possible) during the previous colonial era.